Detoxification of sulphidic African shelf waters by blooming chemolithotrophs - Lavik, Gaute; Stührmann, Torben; Brüchert, Volker; Van der Plas, Anja; Mohrholz, Volker; Lam, Phyllis; Mußmann, Marc; Fuchs, Bernhard M.; Amann, Rudolf; Lass, Ulrich; Kuypers, Marcel M. M. (Nature, 2009)
Algae that bloom unnoticed Data obtained by RV Alexander von Humboldt in waters off the Namibian coast reveal that an area of about 7,000 km 2 of African coastal shelf, covered by sulphidic water, was detoxified by the action of bacteria: the biologically harmful sulphide was oxidized to non-toxic colloidal sulphur and sulphate. Eutrophication of coastal waters, often due to human activity, can lead algal blooms causing severe oxygen depletion and the episodic occurrence of hydrogen sulphide with disastrous consequences for the ecosystem. The discovery that sulphide can be completely consumed by bacteria in subsurface waters, and can thus be overlooked by remote sensing or monitoring of shallow coastal waters, suggests that sulphidic bottom waters on continental shelves may be more common than was thought, so could have an important but previously neglected effect on benthic communities. Eutrophication of coastal waters can cause sulphide blooms, which are toxic to marine life. It is shown that these blooms can be rapidly detoxified by sulphide-oxidizing bacteria. This finding suggests that sulphide blooms may occur more frequently than previously appreciated and that the responsible bacterial groups are important to protect coastal ecosystems. Coastal waters support ∼90 per cent of global fisheries and are therefore an important food reserve for our planet 1 . Eutrophication of these waters, due to human activity, leads to severe oxygen depletion and the episodic occurrence of hydrogen sulphide—toxic to multi-cellular life—with disastrous consequences for coastal ecosytems 2 , 3 , 4 , 5 . Here we show that an area of ∼7,000 km 2 of African shelf, covered by sulphidic water, was detoxified by blooming bacteria that oxidized the biologically harmful sulphide to environmentally harmless colloidal sulphur and sulphate. Combined chemical analyses, stoichiometric modelling, isotopic incubations, comparative 16S ribosomal RNA, functional gene sequence analyses and fluorescence in situ hybridization indicate that the detoxification proceeded by chemolithotrophic oxidation of sulphide with nitrate and was mainly catalysed by two discrete populations of γ- and ε-proteobacteria. Chemolithotrophic bacteria, accounting for ∼20 per cent of the bacterioplankton in sulphidic waters, created a buffer zone between the toxic sulphidic subsurface waters and the oxic surface waters, where fish and other nekton live. This is the first time that large-scale detoxification of sulphidic waters by chemolithotrophs has been observed in an open-ocean system. The data suggest that sulphide can be completely consumed by bacteria in the subsurface waters and, thus, can be overlooked by remote sensing or monitoring of shallow coastal waters. Consequently, sulphidic bottom waters on continental shelves may be more common than previously believed, and could therefore have an important but as yet neglected effect on benthic communities.